Brazilian Propaganda : Legitimizing an Authoritarian Regime - Schneider, Nina, 1980- (Book collections on Project MUSE., 2014)
This book uses the case study of Brazil's military government from 1964 to 1985 to provide a rare inside look at how propaganda is successfully created and distributed.